Matching with Waiting Times: The German Entry-Level Labor Market for Lawyers - Philipp D. Dimakopoulos; C.-Philipp Heller (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We study the allocation of German lawyers to regional courts for legal trainee-ships. Because of excess demand in some regions lawyers often have to wait before being allocated. The currently used B̈erlinm̈echanism is not weakly Pareto efficient, does not eliminate justified envy and does not respect improvements. We introduce a mechanism based on the matching with contracts literature, using waiting time as the contractual term. The resulting mechanism is strategy-proof, weakly Pareto efficient, eliminates justified envy and respects improvements. We extend our proposed mechanism to allow for a more flexible allocation of positions over time.
Keywords: D47; D82; C78; H75; I28; 330; many-to-one matching; matching with contracts; stability; slot-specific choice functions; waiting time; legal education